The possible use of local bentonite as an oil well cement additive - Samsuri, Ariffin; Junin, Radzuan (1998)
Bentonite was the first material extensively used as an oil well cement extender due to its ability to absorb large amounts of water. In oil well cementing, bentonite allows the use of increases amounts of mix water without water separation, which increased water content results in a lower density, greater, yield and reduces that fluid loss of cement slurry. Since it is a highly colloidal type of bentonite from Wyoming, United States, the problem of quality and its quality control have been observed in the field in recent years. In addition, the used of Wyoming bentonite also increase the material cost. Therefore, the studies have been carried out to see the possibility of using local bentonite as an oil well cement additive. To be acceptable for use in cement slurries, the bentonite must meet API Specification as set forth in API Specification 10A. Therefore, this paper dicusses the results of laboratory studies on the potential of utilizing bentonite from Sabah as an oil well cement additive. The studies included chemical analysis, characteristics and performance tests that had been conducted according to ASTM and API Specification. The results show that montmorillonite is the main mineral detected by XRD analysis in the fresh bentonite samples from Tawau and Lahad Datu areas which have CEC values ranging from 25.0 meq/100 gram to 40 meq/100 gram, depending on the grain size. The bigger the grain size, the higher CEC values will be. The performance test results which included thickening time, fluid loss, free water and compressive strength show that cement slurries with local bentonite can meet the API Specification. In general, the local bentonite has potential to be used as an oil well additive.